Pendampingan Kegiatan Keagamaan Oleh Mahasiswa KKN Di Nagari Padang Toboh Ulakan - Husnul Fadhilah; Suci Ayu Lasmini; Ara Fathil Aida; Ahmad Faiz; Sadra Basir; Hamzah Irfanda; Nurva Dillatul Vatin (Institut Agama Islam Sumatera Barat, 2025)
The Community Service Program (KKN) is a form of student community service that aims to provide real contributions to various aspects of social, educational, and religious life. This article discusses the role of KKN students in religious activities in Nagari Padang Toboh Ulakan, a village with a strong religious tradition and a surau as a center of religious activities. The main problems faced are the low interest in reading the Qur'an among the younger generation and limited religious literacy that supports the formation of Islamic morals. Through a Participatory Action Research (PAR) approach, KKN students implemented several programs, including daily Qur'an recitation, religious studies after dawn, weekly wirid, Fahmil Al-Qur'an competitions between MDTA (Islamic Madrasahs), and teaching assistance at MDTA. These activities involved the active participation of the community and local religious institutions. The results of the implementation indicate that students play an important role as facilitators and agents of change in increasing Qur'an literacy, strengthening religious traditions, and fostering religious awareness among the younger generation. Thus, the presence of KKN students not only provides short-term positive impacts, but also encourages the content of religious development in Nagari Padang Toboh Ulakan